Study the electrical stress withstand properties of heated refined bleached and deodorized palm oil dielectrics - Hadi Kadim, Ilham Abdul (2015)
The world’s energy requirement has been dominated by petroleum oil for centuries in many application fields, including transportation, household, and electricity. Mineral oil as an important insulating material in transformers has been used more than 150 years. Mineral oil application in power system equipment can be potentially hazardous to the environment especially when there are any incidents during operational time like transformer explosion which may cause a spill of oil to the soil or water stream. Due to the concerns about the deducing petroleum resources and the environmental issues, the alternative insulating oil with biodegradable characteristics has been attracted lots of attentions for a couple of decades. In this thesis, the dielectric properties of a type of mineral oil (Transformer Oil) and a type of vegetable oil (RBDPO) were investigated, and the effect of heating on their dielectric properties were studied as well. Since the heating effects on the dielectric properties of insulating oil, such as breakdown voltage, kinetic viscosity, pH Value, In addition to the partial discharge performance under the heating condition was studied. All the experiments in this project were conducted at a heating condition for the temperatures of 25⁰C, 50⁰C, 70⁰C, and 90⁰C. RBDPO was compared with petroleum based mineral oil. The results of experiments incorporated showed the potential of oil as a substitute RBDPO to the petroleum-based mineral oil. The BDV tests incorporated showed that the high BDV for RBDPO enables it to avoid a breakdown when the electric stressed. The average value of the BDV increases slightly as the increase of the temperature. The potential of RBDPO, as an electrical insulating liquid, to replace the petroleum-based mineral oil also can be concluded from the viscosity and acidity tests. From the experiments and analysis, it has been proven that the RBDPO is a good insulation because the kinetic viscosity for RBDPO is low and very near from the viscosity of the petroleum-based mineral oil after heating the oil to 50⁰C and above.